2020
DOI: 10.1007/s00439-019-02108-3
|View full text |Cite
|
Sign up to set email alerts
|

Human genetics of life-threatening influenza pneumonitis

Abstract: Influenza viruses infect millions of people around the globe annually, usually causing self-limited upper respiratory tract infections. However, a small but non-negligible proportion of patients suffer from life-threatening pulmonary disease. Those affected include otherwise healthy individuals, and children with primary infections in particular. Much effort has been devoted to virological studies of influenza and vaccine development. By contrast, the enormous interindividual variability in susceptibility to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 81 publications
(131 reference statements)
3
45
0
Order By: Relevance
“…This is consistent with findings that patients with IEIs that specifically affect B-and T-cell development or function do not exhibit increased susceptibility to severe disease caused by influenza infection. 31,32 Our findings that patients with CVID comprised a large proportion of our cohort (>30%), and that 4 of these patients died (45% of all deaths), may infer that intact humoral immunity is important for host defense against SARS-CoV-2. However, these patients were generally older than the rest of the cohort (median age range, 45-54 years), and many had pre-existing health conditions that predispose to severe COVID-19 in the general population (lung disease in ;50%, kidney/heart/gut/liver disease in ;20%; Table II).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This is consistent with findings that patients with IEIs that specifically affect B-and T-cell development or function do not exhibit increased susceptibility to severe disease caused by influenza infection. 31,32 Our findings that patients with CVID comprised a large proportion of our cohort (>30%), and that 4 of these patients died (45% of all deaths), may infer that intact humoral immunity is important for host defense against SARS-CoV-2. However, these patients were generally older than the rest of the cohort (median age range, 45-54 years), and many had pre-existing health conditions that predispose to severe COVID-19 in the general population (lung disease in ;50%, kidney/heart/gut/liver disease in ;20%; Table II).…”
Section: Discussionmentioning
confidence: 91%
“…39,40 In the first study, 650 patients with lifethreatening COVID-19 were studied by whole-exome sequencing under the hypothesis that severe COVID-19 is allelic with severe influenza 39 or that genes biologically related to these loci would be involved. 31,32 Indeed, 3.5% of patients had known (AR IRF7 and IFNAR1 deficiency, autosomal-dominant TLR3, TICAM1, TBK1, and IRF3 deficiency) and new (autosomal-dominant UNC93B1, IRF7, IFNAR1, and IFNAR2 deficiency) genetic defects abolishing induction or amplification of type I IFNs. 39 In the second study, neutralizing autoantibodies against type I IFNs were found in 10.2% of 987 patients with life-threatening COVID-19 pneumonia, resulting in low or undetectable serum levels of IFN-a during acute disease; 94% of the patients with autoantibodies were male.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, among the candidate genes identified, we found the well-known host viral restriction factors encoded by IFITM3, OAS3, and MX1, as well as critical TFs (IRF7, IRF9) involved in the severity of IAV-infection both in mice and humans (Allen et al, 2017;Ciancanelli et al, 2016;Zhang, 2020). Notably, IFITM3 expression was higher in nonclassical and intermediate monocytes relative to classical monocytes, and presented higher expression in ex vivo resistant versus susceptible individuals across all subsets ( Figure 6D).…”
Section: Basal Differences In Activation Of Antiviral Responses Corrementioning
confidence: 93%
“…Genetic variation in such proteins can affect susceptibility to infectious disease (; Ciancanelli, Abel, Zhang, & Casanova, 2016; Karlsson, Kwiatkowski, & Sabeti, 2014; Pittman, Glover, Wang, & Ko, 2016; Q. Zhang, 2020). Perhaps the best-known mutation conferring genetic resistance to viral infection is the Δ32 variant of the HIV-1 co-receptor C-C chemokine receptor type 5 ( CCR5 ) (Carrington, Dean, Martin, & O’Brien, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Additional mutations associated with severe influenza (reviewed in (Ciancanelli et al, 2016; Q. Zhang, 2020)) have been described in the complement factor CD55/DAF (Chatzopoulou, Gioula, Kioumis, Chatzidimitriou, & Exindari, 2019), the pulmonary surfactant protein SFTPA2 (Herrera-Ramos et al, 2014), the protease TMPRSS2 (Cheng et al, 2015), the endothelial transcriptional activator GATA2 (Sologuren et al, 2018), interferon regulators IRF7 and IRF9 (Bravo Garcia-Morato et al, 2019; Ciancanelli et al, 2015; Hernandez et al, 2018), and the endosomal dsRNA receptor TLR3 (Esposito et al, 2012; Hidaka et al, 2006; Lim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%